Analisis Perencanaan Sistem Jaringan Distribusi Listrik dan Perkembangan Beban Pada Perumahan The Grand Kenjeran Surabaya - Epiwardi; Ruwah Joto; Muhammad Urfan Barran Rusyda Marzuq (Elposys: Jurnal Sistem Kelistrikan, 2022)
Planning here aims to get an optimal service flexibility so that it is able to quickly anticipate the growth of electrical energy and how dense the load that must be served. So that the planning of the electricity distribution network system must pay attention to the load conditions in the field, this is intended so that the planned distribution network system can still work well for the next few years. The data collection method used is in the form of field observations which aim to determine field conditions and obtain load data that will be planned. The results of research conducted at The Grand Kenjeran Surabaya housing show that there are 76 housing units to be built in this housing. The 76 housing units will be divided into 4 blocks D, E, F, G and are planned with an initial power of 5500 VA for each housing unit along with Public Road Planning in residential areas. Taking into account field conditions, ground cables are used as a distribution network system which includes SKTM and SKTR. The total power obtained is 435,107.5 VA and is served by 3 units of distribution transformer using Pole Transformer Substation, 3 PHB-TR, 12 Main PHB, and 3 Branch PHB. The magnitude of the possible voltage drop is around 0.97% for medium voltage, 0.3% - 0.92% for Main PHB group, 0.7% - 1.54% for Branch PHB group.